Bishop Benedetto of Cephalonia, 1207– post 1239. - Kouroupakis, Apostolos; Schabel, Christopher David (Mediterranean Historical Review, 2017)
A fresh look at the few sources concerning Bishop Benedetto of Cephalonia, within the context of the recently revised history of the rule of Count Maio on the island, reveals that this first Latin bishop was a relative of the count who had an eventful and colourful rule lasting over 32 years. This chronological survey of Benedetto’s tenure illustrates the transition from a Greek to a Latin episcopacy in Frankish Greece, the restructuring of the Church following the Fourth Lateran Council, the shifting allegiances of the secular powers, and finally the problems caused by the frequently unlettered and scandalous resident prelates who ruled during the first decades after the Fourth Crusade: Benedetto was accused of simony, ignorance, negligence and sexual incontinence.